KOMUNIKASI TERAPEUTIK PERAWAT PADA FASE KERJA DENGAN KEPUASAN PASIEN TERHADAP PELAYANAN KEPERAWATAN DI INSTALASI RAWAT INAP - Irma M. Yahya; Silvia Dewi M. Riu; Sintia Yefi Ering (PT. Hasba Edukasi Mandiri, 2026)
Dissatisfaction in patients can be caused by several factors such as communication failures, time constraints, quality of products or services, quality of care, price, and costs.The purpose of this study is to determine the relationship between nurses' therapeutic communication during the working phase and patient satisfaction with nursing services in the inpatient installation of RSU GMIM Pancaran Kasih Manado. The research uses a cross-sectional design.The sample in this study consisted of 48 respondents using the purposive sampling technique.The collection of therapeutic communication and patient satisfaction data used a questionnaire, which was analyzed using the chi-square statistical test. The results of the therapeutic communication study showed that the majority rated it as good, with 31 respondents (64.6%).the highest patient satisfaction was found to be good, with 32 respondents (66.7%).The chi-square test result obtained a p-value of 0.000 where < α 0.05. Conclusion: There is a relationship between the nurse's therapeutic communication in the working phase and patient satisfaction with nursing services in the inpatient installation of RSU GMIM Pancaran Kasih Manado.